2019
DOI: 10.1002/ana.25423
|View full text |Cite|
|
Sign up to set email alerts
|

A randomized study of solriamfetol for excessive sleepiness in narcolepsy

Abstract: Objective Solriamfetol (JZP‐110) is a selective dopamine and norepinephrine reuptake inhibitor with wake‐promoting effects. This phase 3 study (NCT02348593) evaluated the safety and efficacy of solriamfetol in narcolepsy. Methods Patients with narcolepsy with mean sleep latency <25 minutes on the Maintenance of Wakefulness Test (MWT), Epworth Sleepiness Scale (ESS) score ≥10, and usual nightly sleep ≥6 hours were randomized to solriamfetol 75, 150, or 300 mg, or placebo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
121
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 279 publications
(129 citation statements)
references
References 36 publications
(41 reference statements)
5
121
1
1
Order By: Relevance
“…The efficacy and safety of solriamfetol were also evaluated in a phase III, 12-week randomised, double-blind, placebocontrolled trial from the TONES (Treatment of Obstructive Sleep Apnea and Narcolepsy Excessive Sleepiness) phase III programme-the TONES 2 study [31]. Adults with narcolepsy with or without cataplexy were randomly assigned to fixed doses of solriamfetol (75,150, 300 mg/day) or placebo.…”
Section: Efficacymentioning
confidence: 99%
See 1 more Smart Citation
“…The efficacy and safety of solriamfetol were also evaluated in a phase III, 12-week randomised, double-blind, placebocontrolled trial from the TONES (Treatment of Obstructive Sleep Apnea and Narcolepsy Excessive Sleepiness) phase III programme-the TONES 2 study [31]. Adults with narcolepsy with or without cataplexy were randomly assigned to fixed doses of solriamfetol (75,150, 300 mg/day) or placebo.…”
Section: Efficacymentioning
confidence: 99%
“…Discontinuations due to AEs were reported for 7% of solriamfetol-treated participants in the short-term phase IIb study and for 5.1% of solriamfetol-treated participants (1.7%, 5.1% and 8.5% for the 75, 150 and 300 mg groups) in the short-term phase III study, compared with 4% and 2% in placebo-treated participants, respectively [30,31]. SAEs were reported for 4.5% (2/44) and 0.6% (1/177) of solriamfetol-treated participants in the phase IIb and III studies, respectively (no SAEs with placebo in either study) [30,31].…”
Section: Safetymentioning
confidence: 99%
“…With only a moderate effect of current stimulants in subpopulations of people with IH, the emergence of a new effective stimulant for the treatment of narcolepsy, solriamfetol [39], holds promise for the treatment of excessive daytime sleepiness in IH.…”
Section: Solriamfetolmentioning
confidence: 99%
“…In phase 3 trials in patients with narcolepsy and OSA, solriamfetol demonstrated reductions in excessive daytime sleepiness measured on the patient-reported Epworth Sleepiness Scale, 3 and improvement in objective assessment of wakefulness using the Maintenance of Wakefulness Test, that were statistically significantly greater than placebo. [4][5][6] Significantly higher percentages of participants treated with solriamfetol in these trials also reported improvement on the Patient Global Improvement of Change scale relative to placebo at all evaluated time points.…”
mentioning
confidence: 99%